Stroke care during the COVID‐19 pandemic: experience from three large European countries. (27th June 2020) - Bersano, A.; Kraemer, M.; Touzé, E.; Weber, R.; Alamowitch, S.; Sibon, I.; Pantoni, L.
Abstract : In order to cope with the exponentially increasing number of patients infected with SARS‐CoV‐2, European countries made enormous efforts to reorganize medical assistance and several diseases, including stroke, were particularly impacted. We report the experience of stroke neurologists from three European countries (Italy, France and Germany) that faced the pandemic at diverse time points and with different approaches, depending on their resources and healthcare system organization. Pre‐hospital and in‐hospital acute stroke pathways were reorganized to prioritize COVID‐19 management and, in severely affected regions of Italy and France, stroke care was centralized to a limited number of centers, whereas the remaining stroke units were dedicated to patients with COVID‐19. Access to acute stroke diagnostics and time‐dependent therapies was limited or delayed because of reduced capacities of emergency services due to the burden of patients with COVID‐19. A marked reduction in the number of patients presenting with transient ischaemic attack and stroke was noted in the emergency departments of all three countries. Although we only have preliminary data, these conditions may have affected stroke outcome. These indirect effects of the COVID‐19 pandemic could negate the efforts of stroke neurologists over the last few years to improve outcome and reduce mortality of stroke patients. Although the SARS‐CoV‐2 infection rate is slowing down in Europe, the effects of ending lockdown in the next months are unpredictable. It is important for the European and world stroke community to share what has been learned so far to be plan strategies to ensure stroke care in the future and upcoming challenging times.